Sistem Pakar Berbasis Aturan untuk Mendiagnosis Kanker Payudara Menggunakan Certainty Factor - Chiva Olivia Bilah; Ardian Infantono (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
As we know that cancer has various types such as lung, cervical, breast, colon and so on.Breast Cancer (BC) is a very serious health problem in Indonesia. Breast cancer ranks first as the most dangerous and is considered a 'killer'. Therefore, a strategy for early diagnosis of BC is needed to reduce the risk of death from breast cancer. This study uses an expert system using the forward chaining method and certainty factor to diagnose BC early based on the type of symptoms that exist. The development of the expert system in this study uses the CLIPS programming la